Foreign direct investment in China : winners and losers - Hale, Galina (World Scientific, 2012)
This book provides a comprehensive analysis of the effects that foreign direct investment into China has had on the productivity, exporting activity, and innovation of Chinese domestic firms, as well as on the nation's labor markets. The analysis relies on the most complete data available and state-of-the-art statistical analysis. The book also includes a critical overview of existing theoretical and empirical literature on these issues and is meant to provide guidance to researchers in the area of FDI effects in general, as well as those interested in studying the Chinese economy.